Hadith #3730 - Sahih al-Bukhari - Ubada bin al-Waleed bin 'Ubada عبادة بن الوليد بن عبادة بن الصامت (Sahih al-Bukhari)
I was one of the Naqibs who gave the (‘Aqaba) Pledge of Allegiance to Allah’s Messenger (ﷺ) . We gave the pledge of allegiance to him that we would not worship anything other than Allah, would not steal, would not commit illegal sexual intercourse, would not kill a person whose killing Allah has made illegal except rightfully, would not rob each other, and we would not be promised Paradise jf we did the above sins, then if we committed one of the above sins, Allah will give His Judgment co
Grade: Sahih

Hadith #6618 - Sahih al-Bukhari - Ubada bin al-Waleed bin 'Ubada عبادة بن الوليد بن عبادة بن الصامت (Sahih al-Bukhari)
I was among those Naqibs (selected leaders) who gave the Pledge of allegiance to Allah’s Messenger (ﷺ). We gave the oath of allegiance, that we would not join partners in worship besides Allah, would not steal, would not commit illegal sexual intercourse, would not kill a life which Allah has forbidden, would not commit robbery, would not disobey (Allah and His Apostle), and if we fulfilled this pledge we would have Paradise, but if we committed any one of these (sins), then our case will be
Grade: Sahih